Topographic controls on plateau icefield recession : insights from the Younger Dryas Monadhliath Icefield, Scotland - Boston, Clare M.; Lukas, Sven (Journal of Quaternary Science, 2019)
Plateau icefields are a common form of mountain ice mass, frequently found in mid-latitude to high-arctic regions and increasingly recognized in the Quaternary record. Their top-heavy hypsometry makes them highly sensitive to changes in climate when the equilibriaum line altitude (ELA) lies above the plateau edge, allowing ice to expand significantly as regional ELAs decrease, and causing rapid recession as climate warms. With respect to future climate warming, it is important to understand the controls on plateau icefield response to climate change in order to better predict recession rates, with implications for water resources and sea-level rise. Improving knowledge of the controls on glacier recession may also enable further palaeoclimatic information to be extracted from the Quaternary glacial record. We use the distribution of moraines to examine topographic controls on Younger Dryas icefield recession in Scotland. We find that overall valley morphology influences the style of recession, through microclimatic and geometric controls, with bed gradient affecting moraine spacing. Ice mass reconfiguration may occur as recession progresses because ice divide migration could alter the expected response based on hypsometric distribution. These results add to a growing body of research examining controls on glacier recession and offer a step towards unravelling non-linear ice mass behaviour.